2018
DOI: 10.1183/13993003.02173-2017
|View full text |Cite
|
Sign up to set email alerts
|

Sputum proteomics and airway cell transcripts of current and ex-smokers with severe asthma in U-BIOPRED: an exploratory analysis

Abstract: Severe asthma patients with a significant smoking history have airflow obstruction with reported neutrophilia. We hypothesise that multi-omic analysis will enable the definition of smoking and ex-smoking severe asthma molecular phenotypes.The U-BIOPRED cohort of severe asthma patients, containing current-smokers (CSA), ex-smokers (ESA), nonsmokers and healthy nonsmokers was examined. Blood and sputum cell counts, fractional exhaled nitric oxide and spirometry were obtained. Exploratory proteomic analysis of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 43 publications
2
59
0
Order By: Relevance
“…Levels of CYP1B1 transcripts in human lung were elevated in smokers as shown by Port et al (2004) in smokers bronchial mucosa. Takahashi et al (2018) found that CYP1B1 transcripts were increased in bronchial brushings from currently smoking asthmatics compared with ex-smoking and non-smoking asthmatics and non-smoking healthy individuals. Conversely, Walters et al (2017) found that in bronchial brushings obtained from small airway epithelium of individuals smoking water pipe (a common form of tobacco use in the Middle East) CYP1B1 transcripts were reduced compared with non-smokers, but the CYP1B1 gene was hypomethylated.…”
Section: Xenobiotica-metabolizing Enzymes In the Human Lungmentioning
confidence: 89%
See 1 more Smart Citation
“…Levels of CYP1B1 transcripts in human lung were elevated in smokers as shown by Port et al (2004) in smokers bronchial mucosa. Takahashi et al (2018) found that CYP1B1 transcripts were increased in bronchial brushings from currently smoking asthmatics compared with ex-smoking and non-smoking asthmatics and non-smoking healthy individuals. Conversely, Walters et al (2017) found that in bronchial brushings obtained from small airway epithelium of individuals smoking water pipe (a common form of tobacco use in the Middle East) CYP1B1 transcripts were reduced compared with non-smokers, but the CYP1B1 gene was hypomethylated.…”
Section: Xenobiotica-metabolizing Enzymes In the Human Lungmentioning
confidence: 89%
“…In cultured human bronchial epithelial cells, which were obtained from non-smoking donors, ALDH3A1 gene expression was upregulated upon acute exposure to cigarette smoke (Billatos et al 2018). Takahashi et al (2018) found that ALDH3A1 transcripts were overexpressed in bronchial brushings from currently smoking asthmatics compared with ex-smoking and nonsmoking asthmatics and non-smoking healthy individuals. Líbalová et al (2014) reported strong upregulation of ALDH1A3 and ALDH3A1 gene expression upon exposure of A549 cells to the extractable organic matters (EOMs) from the respirable fraction of airborne PM2.5 particles (< 2.5 µm) from three heavily polluted areas of the Czech Republic.…”
Section: Alcohol Dehydrogenase (Adh)mentioning
confidence: 93%
“…The mechanisms underlying smoking-associated asthma is unclear, but it has been considered a T2-low neutrophilic, steroid-resistant phenotype [73]. Putative mechanisms include oxidative stress that mediates epigenetic modifications causing neutrophil and macrophage activation [73].…”
Section: Introductionmentioning
confidence: 99%
“…Putative mechanisms include oxidative stress that mediates epigenetic modifications causing neutrophil and macrophage activation [73]. However, smoking also increases the risk of sensitization to allergens and increases total IgE demonstrating the link between asthma and COPD.…”
Section: Introductionmentioning
confidence: 99%
“…Further investigations of the U-BIOPRED cohort have explored changes in blood and sputum mRNA transcript, protein profiles as well as in bronchial biopsies and brushings. Findings from these studies highlighted molecular signatures related to altered epithelial barriers, responsiveness to steroids, type 2 inflammation and activation in the IL-6 trans signalling pathway (Bigler et al, 2017;Jevnikar et al, 2018;Kuo et al, 2017;Takahashi et al, 2018). As the U-BIOPRED project is still in its data analysis phase, additional results from multiple omics data integration analysis remain to be reported.…”
Section: New Ways To Change the Clinical Definition Of Asthmamentioning
confidence: 99%